Intercambios artísticos en una diócesis transfronteriza - Marta Cendón Fernández (Medievalista)
The Tudense bishopric arises in a space that, with the passing of time, will belong to two countries. The rivers Miño and Limia mark the limits of a diocese whose capital, Tui, had an important role since Roman times, with a fundamental link with Braga. Both, live the historical vicissitudes of the High Middle Ages, and their episcopal sees are restored around the same dates. After that, they tried to rebuild their cathedral buildings: first Braga, with an initial project largely destroyed around 1110 and then Tui after a period of relocation in the monastery of San Bartolomé. The multiplication of donations allows us to think that the new cathedral of Tui began around 1125, with a transept of three naves, similar to that of the cathedral of Santiago and the initial one in Braga, as well as a five-apse chevet, similar to the one proposed by the new bracarense project. These have parallels in other suffragan cathedrals of Braga: in addition to Tui, Ourense and Lamego. Along with all this, there are numerous cross-border artistic exchanges since the diocese of Tui radiates its models throughout its diocesan limits, bordering those of Braga.